Sự biến đổi bệnh lý trên niêm mạc ruột non trâu bị mắc bệnh viêm ruột ỉa chảy - Phạm, Ngọc Thạch (Bộ Giáo dục và Đào tạo, 2013)
The author has collcted specimens from the gut of buffalos affected by enteritis to study the microscopic changes of their gut. Deformaiton of velocity , cryp lieber-kuhn's proliferaiton, oedema in intestinal mucosa, deformation of epithelium cells and inflammatory cell infiltration are seen . Hence, the chenges of absorption surface of the gut and of the villosity wall lead to the excitation of the gut peristalric , resulting in pushing out aliment diarrhoea and reduced absorption. The buffaloes and stune in the growth retardation